2013
DOI: 10.1136/eb-2012-101112
|View full text |Cite
|
Sign up to set email alerts
|

US Medicare data show incidence of hospital-acquired pressure ulcers is 4.5%, and they are associated with longer hospital stay and higher risk of death

Abstract: Commentary on: Lyder CH, Wang Y, Metersky M, et al. Hospital-acquired pressure ulcers: results from the national Medicare patient safety monitoring system study. J Am Geriatr Soc 2012;60:268-8. Implications for practice and research▪ Pressure ulcers (PUs) are common and often occur in older persons and those with multiple comorbidities.▪ Patients with hospital-acquired PUs (HAPUs) have longer hospital stays and higher rates of morbidity and mortality; therefore, prevention and early detection are important pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 4 publications
(3 reference statements)
1
19
0
Order By: Relevance
“…Our results showed that elderly patients with concurrent PIs can accelerate mortality of the elderly patients (HR: 1.78; 95% CI: 1.46‐2.16). Our finding confirmed the previous researches on the relationship between PIs and mortality . There are few reports that have reported the mortality of PIs.…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed that elderly patients with concurrent PIs can accelerate mortality of the elderly patients (HR: 1.78; 95% CI: 1.46‐2.16). Our finding confirmed the previous researches on the relationship between PIs and mortality . There are few reports that have reported the mortality of PIs.…”
Section: Discussionsupporting
confidence: 92%
“…Pressure ulcers not only make a significant independent contribution to the excess length of hospitalisation but also increase significant additional costs for pressure ulcer treatment . Most importantly, pressure ulcers are associated with a higher risk of mortality . Many studies have examined factors associated with SRPU development in cardiovascular surgery patients.…”
Section: Introductionmentioning
confidence: 99%
“…In the international setting, the prevalence varies between 5.0 and 15%, and the incidence between 1.9 and 7% (3,(6)(7)(8)(9) . International studies show a prevalence of 11.1 to 23.2%, and an incidence of 22.5 to 66.6% (10)(11)(12)(13)(14) . Costs of PU management represent a constant challenge for health institutions, since the economic aspect is essential for making decisions related to the use of technologies (15) .…”
Section: Introductionmentioning
confidence: 99%